Changes ın physıologıcal characterıstıcs of gınkgo (gınkgo bıloba l.) Leaves durıng natural yellowıng - Yang, Xıan-Song (Bangladesh Journal of Botany, 2025)
The content of chlorophyll and carotenoids, net photosynthetic rate (PN), maximum quantum yield of photosystem (PS) 2 photochemistry (Fv / Fm), the activity of superoxide dismutase (SOD) and the content of malondialdehyde (MDA) were investigated to survey the physiological characteristics of ginkgo (Ginkgo biloba L.) leaves during natural yellowing. The results showed that the content of total chlorophyll decreased rapidly while the content of carotenoids changed little during leaf natural yellowing, the PN decreased rapidly while the Fv / Fmchanged little during leaf natural yellowing, and the activities of SOD decreased while the content of MDA increased during leaf natural yellowing. Photosynthetic abilities gradually decreased as the leaves yellowing. Bangladesh J. Bot. 54(4): 1083-1087, 2025 (December)